Cardiac amyloidosis: a challenging diagnosis - Graziele Cristina Palancio Morais; Marjorie Moreira Arruda; José Carlos de Aguiar Bonadia; Geanete Pozzan (University of São Paulo, 2014)
Cardiovascular involvement of amyloidosis is present in 90% of cases, which is frequently associated with the primary form of the disease (AL amyloidosis). Clinical manifestations are represented by heart failure due to restrictive myocardiopathy and electrical impulse conduction abnormalities, which are clinically remarkable in up to 50% of the cases. The prognosis of patients with systemic amyloidosis is directly associated with the presence of cardiac involvement, such that survival does not usually exceed 4 months after the onset of heart failure signs and symptoms. The authors report a case of primary systemic amyloidosis, diagnosed only at autopsy, with severe cardiac involvement.